Labour Characteristics Among the Nepalese Indo-Aryan and Tibeto – Burman Ethnic Groups - Thapa, Mira; Manandhar , BL; Sharma, J (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: The study was done to analyze the duration of active phase of first stage of labour and second stage of labour in the Indoaryan and Tibetoburman ethnic population.Methods: A total of 200 patients, 100 from each ethnic groups, Indoaryans and Tibetoburmans, who underwent delivery at Tribhuvan University Teaching Hospital from April 2007 to April 2008 were analyzed. The active phase of first stage of labour and second stage of labour were compared in the two groups . The factors affecting the duration of labour were studied by correlating these factors with duration of labour.Results : Duration of labour was found shorter in Tibetoburmans compared to Indoaryans (155.65 ± 77.56 mins in Indoaryans Vs 134.70 ± 89.182 mins in Tibetoburmans). In primigravidas, mean duration of active phase of first stage of labour was significantly shorter in Tibetoburmans (135.19 ± 53.367 mins)compared to Indoaryans (189.41 ± 65.830mins) but the mean duration of second stage of labour was not significantly shorter. In multigravidas, the mean duration of active phase of first stage of labour was shorter in Indoaryans (120.51 ± 73.663 mins) than in Tibetoburmans (134.17 ± 116.885 mins) but was not statistically significant. But the mean duration of second stage of labour was significantly shorter in Tibetoburmans (26.85 ± 26.534 mins) as compared to Indoaryans (33.73 ± 11.595 mins).Conclusion : Significantly shorter duration of labour is seen in Tibetoburmans as compared to the Indoaryans.